1792 N.J. Laws 850 - (:unkn) unknown (My University, 1792)
Raised the minimum age to 18, and lowered the maximum age to 45. Further, "every non-commissioned Officer and Private of the Infantry (including Grenadiers, Light Infantry and Artillery) until supplied with Ordinance and Field Artillery, shall have a good Musket or Firelock, a sufficient Bayonet and Belt, two spare Flints and a Knapsack, a Pouch with a Box not less than twenty-four Cartridges suited to the Bore of his Musket or Firelock, each Cartridge containing a proper Quantity of Powder and Ball; or with a good Rifle, Knapsack, Pouch and Powder-Horn, twenty Balls suited to the Bore of his Rifle, and a Quarter of a Pound of Powder; and shall appear so armed, accoutred and provided, when called out to exercise or into Service.
Keywords: MILITIAS; REQUIRED POSSESSION